Crop Coefficient of Tomato under Deficit Irrigation and Mulch Practices at Kano River Irrigation Project, Nigeria - Zakari, M. D.; Audu, I.; Igbadun, H. E.; Nasidi, N. M.; Ibrahim, A.; Shitu, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This work determined the effects of deficit irrigation and mulching practices on crop coefficient (Kc) of tomato in the Kano River Irrigation Project (KRIP) Kadawa, Kano, Nigeria. Experiments comprised of four levels of water application depths (40, 60, 80, and 100% of weekly reference evapotranspiration) and four levels of mulching (No-Mulch (NM), Rice-Straw-Mulch (RSM), Wood-Shaving-Mulch (WSM) and White-Polyethylene-Mulch (WPM)) was conducted to examine changes in Kc value. The mean Kc values (early, developmental, mid and late stages) of fully irrigated treatments were 0.70, 0.81, 1.07 and 0.78; 0.64, 0.76, 0.99 and 0.71; 0.60, 0.73, 0.94 and 0.69; and 0.53, 0.66, 0.86 and 0.62 for NM, RSM, WSM and WPM respectively while that of deficit irrigation ranged from 0.17 to 1.13 across the treatments, noting that the highest Kc was observed under NM treatments. Statistical analysis reveals that the effect of various levels of irrigation and mulching practices on Kc of tomato was highly significant at P＜0.05 level of significance with a high mean value of 1.13 obtained at I100 and NM respectively. It was concluded to encourage tomato farmers in KRIP to adopt the use of their rice straw for mulching cum deficit irrigation (20%) towards conserving irrigation water for sustainability. Also, results obtained from this study can be used as a guide to farmers in irrigating tomato crop and to engineers in the design of irrigation systems.